The Effect of Work Communication and Work Motivation to Employee Performance at PT. Catur Mitra Sejati Sentosa - Miftachul Choir; Elok Damayanti; Joko Suyono (Jurnal Ekonomi, 2021)
This research intends to determine: (1) the effect of work communication on employee performance, and (2) the effect of work motivation on employee performance. The population in this research are all employees of PT. Catur Mitra Sejati Sentosa, totaling 65 employees. The sample utilized in this research is the entire population of 65 employees, thus it is called a population research. Instrument testing was carried out at PT. Catur Mitra Sejati Sentosa. The validity test used correlation product moment, while the reliability test used Spearman Brown which processed by using SPSS 18.0 for Windows. In the validity test of work communication, there are 9 statements and all are valid. In the validity test of work motivation, there are 5 statements and all are valid. In the validity test of employee performance, there are 9 statements and all are valid. Furthermore, the classical assumption test includes multicollinearity test and heteroscedasticity test. Meanwhile, the hypothesis test in this research applies multiple regression analysis and the coefficient of determination. The results of this research indicate that: (1) Work Communication (X1) has a partially significant influence on the Employee Performance variable (Y). This is demonstrated by the magnitude of the significance value of 0.029 which is smaller than 0.05. In accordance with these results, it can be concluded that work communication has a significant effect on the employee performance of PT. Catur Mitra Sejati Sentosa. (2) Work Motivation (X2) has a partially significant influence on Employee Performance (Y). This is indicated by the magnitude of the significance value of more than 0.008 which is smaller than 0.05. According to these results, it can be inferred that work motivation has a significant effect on the employee performance of PT. Catur Mitra Sejati Sentosa. (3) Work Communication (X1) and Work Motivation (X2) have a significant effect simultaneously on the Employee Performance variable (Y). This is revealed by the magnitude of the significance value of more than 0.008 which is smaller than 0.05. Based on these results, it can be concluded that work motivation has a significant effect on the employee performance of PT. Catur Mitra Sejati Sentosa. (3) Work Communication (X1) and Work Motivation (X2) have a significant effect simultaneously on the Employee Performance variable (Y).